Psycho-Hermeneutic Approach to Self-Acceptance as a Factor of Psychological Well-Being of the Contemporary Woman - Maystruk, Victoria (Psychological Prospects Journal, 2018)
Psycho-hermeneutic approach to self-acceptance as a factor of psychological well-being of the contemporary woman based on the auto narratives is highlighted in the article. The methodological basis is represented by principle of social constructivism considering the dynamics of personal development and its reflection in the texts. The suggested scheme of the psycho-hermeneutic analysis contains the form and features of experience revealing, main life events, the peculiarities of their interpretation, context and mechanisms of personal development. The predominant type of narrative for women with low level of self-acceptance is ambivalent type. The low level of personal identity, undeveloped self-image was revealed in the narratives of women with low level of self-acceptance. The components of well-being in the narratives were defined. The unconditional self-acceptance, competence and autonomy are underdeveloped, whereas interpersonal relations, abstract lifegoals and obscure trajectory of self-developments were represented.The predominant type of narrative for women with middle level of self-acceptance is positive and negative types. The middle level of personal identity, life goals and developed self-image were revealed in the narratives of women with middle level of self-acceptance. The main  type of narrative for women with high level of self-acceptance is positive type.All components of well-being in the narratives were defined. The unconditional self-acceptance, competence and autonomy,interpersonalrelations, concrete lifegoals and clear trajectory of self-developments were represented. Notwithstanding the negative or traumatic events representations in the narratives, all these events are interpreted and highly aware by the women.
Keywords: psycho-hermeneutics, self-acceptance, psychological well-being, auto-narrative.